NCFSK bit-error rate with unsynchronized slowly fading interferers. - Chong, P.H.J.
An expression for the bit-error rate (BER) of noncoherent frequency-shift keying with a nonfaded desired signal in the presence of N Rayleigh-faded unsynchronized cochannel interferers (UCCIs) and additive white Gaussian noise is first derived. This result can be used to obtain the BER for a faded desired signal. For a large number of UCCIs, numerical evaluation of this expression can be quite time-consuming. An approximate method that yields fairly accurate results is thus described. Numerical results show that for a Rician-faded desired signal with a strong specular component in an interference-limited environment, the BER decreases slightly with N whereas for a Rayleigh-faded desired signal, the BER varies very little with N. A comparison to the BER performance with synchronized cochannel interferers is also provided
Keywords: AWGN; BER performance; NCFSK bit-error rate; Rayleigh-faded unsynchronized cochannel interferers; Rician-faded desired signal; Additive white Gaussian noise; Approximate method; Bit-error rate; Cellular systems; Interference-limited environment; Noncoherent frequency-shift keying; Nonfaded desired signal; Synchronized cochannel interferers; Unsynchronized slowly fading interferers